Student Process Skills on Temperature and Heat Materials - Azhar, Azhar; Megahati S, Ruth Rize Paas (RADINKA JAYA UTAMA PUBLISHER, 2022)
This study aims to describe and determine the differences in students' physics process skills through the LKS based on Natural Exploration (JAS) on temperature and heat at SMAN 2 XIII Koto Kampar. The research design used in this study was an intact-group comparison design. The data collection technique in this study was giving tests to the experimental and control classes, after learning through LKS based on Exploring the Surroundings. The average absorption power of the experimental class is 80% in the good category, while the control class is 74% in the good category. Based on students' absorption, it can be said that learning in the experimental and control classes is effective. Classical student learning completeness in the experimental class is 84% and in the control class is 62.5% otherwise incomplete. The classical completeness of the process skill indicator in the experimental class is 100% and in the control class is 75%. In classical completeness, the indicator of process skills in the experimental class is declared complete and the control class is declared incomplete. After the t-test was conducted, it was found that there was a significant difference in physics process skills through LKS based on Exploring the Surroundings by using ordinary LKS.